EDUKASI ANAK-ANAK MENINGKATKAN PENGHIJAUAN DENGAN MENANAM TANAMAN LOKAL DI PANTAI PASIR PADI - Permatasari, Anggun; Iskandar, Yunita; Sudianti, Selvi; Sartika, Sartika; Dirahmad, Ernita; Okta, Andini; Gandhi, Sonia; Nazwa, Dhea; Dwi, Putri; Yolanda, Yolanda; Bayu, Ahmad; Arif, Arif (Nindikayla Institute, 2023)
Pasir Padi Beach is a beach that has enormous potential to attract both domestic and foreign tourists. However, this potential is not matched by inadequate beach conditions, instead various problems are encountered, one of which is the hot and barren beach conditions. One effort to overcome this problem is by planting ketapang and kemunting trees on the coast. Apart from rehabilitating land in coastal areas, this effort also aims to preserve environmental greenery so that it is maintained, usually it is also often used as a shade plant, especially ketapang trees. Planting activities include planting planning, planting preparation and planting. Planting planning includes: Plans for determining the location, the required number of seeds, and how to arrange the timing. The results achieved from the ketapang and kemunting tree planting program activities are to prevent coastal erosion, reduce land aridity, fertilize the soil, and provide shade for the community, tourists or visitors to Pasir Padi beach.